Judicial Control over Administrative Discretion in Iraq - Mohammed Noori Ali; Nurhafilah Musa; Mohamad Rizal bin Abd Rahman (Hasanuddin Law Review, 2022)
Discretionary powers allow administrative authorities to fulfil public interest through their flexibility to act in circumstances not anticipated by law. Yet, in Iraq discretionary power remains contentious as it may undermine individual rights. This article examines the concept of discretionary powers, particularly how Iraq's administrative authorities exercise such powers and the role of Iraq's administrative judiciary in reviewing any administrative decisions. Analysis of material from primary and secondary sources reveals that Iraq's legal system permits administrative authorities to exercise broad discretionary decision-making powers. This precipitate abuses. Further, the restriction of Iraq's administrative judiciary and the absence of suitable legislation prevent administrative court judges from effectively curbing administrative arbitrariness. Legal transformations are necessary to streamline the scope for discretion by requiring Iraq's administrative authorities to provide reasoned decisions and better empower the administrative judiciary to check the administration's arbitrariness. As well, judges need more training on the operations of administrative courts.